2018
DOI: 10.1111/petr.13147
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcome of chronic high Epstein‐Barr viral load carriage in pediatric kidney transplant recipients

Abstract: The development of EBV infection and PTLD is normally associated with a high EBV viral load in peripheral blood. Observations have previously identified existence of a CHL carrier state that demonstrated variable outcomes based upon the organ which was transplanted. Data defining the incidence and outcome of CHL in pediatric KTx are not well described. The charts of children undergoing isolated KTx at Children's Hospital of Pittsburgh between January 2000 and December 2014 were retrospectively reviewed. EBV lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…The incidence of PTLD was 45% in persistent high load carriers in a cohort of heart transplant recipients 8 . The same center reported that the incidence is lower in liver transplant (3%) and intestinal transplant (11%) recipients and lowest in kidney transplant patients(0%) 16‐18 A subset analysis from a prospective randomized double blind trial of steroid withdrawal, conducted by the North American Pediatric Renal Trials and Collaborative Studies (NAPRTCS), showed a 6.9% incidence of PTLD in patients with persistent viral load 19 . In our study, 1 (No‐Rituximab patient) of 13 (7.6%) patient with PEBV developed PTLD, which is consistent with the above reported PTLD rate.…”
Section: Discussionmentioning
confidence: 46%
“…The incidence of PTLD was 45% in persistent high load carriers in a cohort of heart transplant recipients 8 . The same center reported that the incidence is lower in liver transplant (3%) and intestinal transplant (11%) recipients and lowest in kidney transplant patients(0%) 16‐18 A subset analysis from a prospective randomized double blind trial of steroid withdrawal, conducted by the North American Pediatric Renal Trials and Collaborative Studies (NAPRTCS), showed a 6.9% incidence of PTLD in patients with persistent viral load 19 . In our study, 1 (No‐Rituximab patient) of 13 (7.6%) patient with PEBV developed PTLD, which is consistent with the above reported PTLD rate.…”
Section: Discussionmentioning
confidence: 46%
“…Some studies suggest that an organ recipient’s EBV load should be monitored every 2 wk for the first 3 mo after surgery, and then every month for the second 3 mo, followed by every 3 mo for the last 6 mo[ 8 ]. However, there is no clear evidence that antiviral therapy helps to reduce a patient’s EBV load or prevent EBV infection[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric heart transplant recipients, the highest rates of PTLD occurred in children transplanted at 1-10 years of age [36]. Interestingly, data from pediatric renal and liver transplant patients identified that EBV seronegative children were more likely to have chronically high viral loads than their seropositive counterparts, but the presence of high viral loads did not correlate with subsequent development of PTLD [39,40].…”
Section: Epstein-barr Virusmentioning
confidence: 99%